Answer:
y = (x + 5)(x - 4)
Step-by-step explanation:
Given
y = x² + x - 20
Consider the factors of the constant term (- 20) which sum to give the coefficient of the x- term (+ 1)
The factors are + 5 and - 4, since
5 × - 4 = - 20 and 5 - 4 = + 1, thus
x² + x - 20 = (x + 5)(x - 4)
y = x2 + x - 20 factors into
y = (x +5) * (x -4)
Answer: 25. -17, -14, -3, 0, 2, 7
26. -26, -21, -13, -1, 5
27. -17, -16, -11, -4, 2, 9
28. -75, -63, -60, -52, 12, 70
x=8
KN=24
LK is congruent to LM
LN is congruent to NL